Assimilable organic carbon cycling within drinking water distribution systems. (15th June 2021) - Pick, Frances C.; Fish, Katherine E.; Boxall, Joby B.
Abstract: A new conceptual model to describe and understand the role of assimilable organic carbon (AOC) within drinking water distribution systems is proposed. The impact of AOC on both drinking water biofilm and water quality was studied using bespoke pipe loop experimental facilities installed at three carefully selected operational water treatment works. Integrated physical, chemical and biological monitoring was undertaken that highlights the central role of biofilms in AOC cycling, forming the basis of the new conceptual model. Biofilms formed under high AOC conditions were found to pose the highest discoloration response, generating a turbidity (4.3 NTU) and iron (241.5 µg/l) response sufficient to have caused regulatory failures from only 20 m of pipe in only 12 months of operation. This new knowledge of the role of biofilms in AOC cycling, and ultimately impacts on water quality, can be used to inform management and help ensure the supply of high-quality, biostable drinking water.